On the performance of some bioinspired genetic operators in complex structures evolution (long version) - Casas, M.; Vico-Vela, Francisco José (My University, 2017)
Indirect encoding methods demand operators that minimize the disruption of conventional operators, widely studied in direct encoding approaches. While some efforts have already been done in this direction, the growing field of Genetics sheds new light on the dynamics of the nucleic acids, and their implications in the evolution of life on Earth. Here we model basic mechanisms of gene duplication and horizontal gene transfer, presenting preliminary results of its application to L-systems evolution. The first interesting finding is that, in the particular simplified framework proposed, most of these operations are only slightly disruptive allowing the structures to evolve without loosing what has been gained in the past. Combining these operators with the traditional point-mutation, insertion and deletion generates interesting dynamics: cycles of genome expansion (duplication / transference) and further tuning (deletion / insertion / mutation) spontaneously emerge. Large populations of L-systems have been evolved to meet simple restrictions on their phenotypic readout. Two case-studies are described: (1) evolution under low selective pressure towards a target aspect, and (2) evolution of a form under changing conditions. Genotypic and phenotypic evolution is discussed, along with a fitness curve that is closer to punctuated equilibrium than to the traditional exponential shape.
Keywords: Algoritmos genéticos; L-systems; Genetic algorithms; Evolutionary computation; Evodevo; Duplication